EVALUASI KINERJA SALURAN IRIGASI DAN BANGUNAN DISTRIBUSI PADA DAERAH IRIGASI AIR NAKAI BATU ROTO BENGKULU UTARA - Besperi; Anisa putri, Salsabillah; Bahri, Samsul; Makmun Reza, Razali (Inersia: Jurnal Teknik Sipil, 2023)
This study intends to analyze the dimensions of the channel, subdivision, and tapping infrastructure. The mainstay discharge was analyzed using the Mock method, the analysis of irrigation water needs was based on Irrigation Planning Standard KP-01, and recalculation of the dimensions of the channel, building for, and tapping building based on the existing discharge and the planned discharge in accordance with Irrigation Planning Standard KP- 03. Rainfall data were analyzed using the algebraic average method. The findings indicated that the highest primary discharge, which occurred in November period I, was 9.21 m3/s. The highest amount of clean water needed in the fields per day (NFR) was 7.55 mm, while the maximum amount of water needed for intake per second (DR) was 1.34 l/sec. The bottom width of the channel (b) is 2.26 m according to the findings of recalculating the BNa 1 primary channel's dimensions using the current discharge. Na.2Ki.A secondary channel measured 0.48 meters for channel bottom width (b). The bottom width of the channel (b) was determined to be 0.601 m as a consequence of recalculating the BNa 1 primary channel's dimensions using the intended discharge. Na.2Ki.A secondary channel measured 0.44 meters for channel bottom width (b). The measurements of the width of the buildings door (b) after being recalculated and tapped based on the current discharge are larger than those of the door's existing dimensions. Keywords: Water Discharge, Irrigation Channels Area, Distribution Building